Expression profile of miRNAs computationally predicted to target PDL-1 in cervical tissues of different histology groups - Leventakou, Danai; Gouloumi, Alina-Roxani; Spathis, Aris; Pouliakis, Abraham; Koufopoulos, Nektarios; Pergialiotis, Vassilios; Drakakis, Peter; Panayiotides, Ioannis G.; Kottaridi, Christine (Frontiers in Cell and Developmental Biology, 2023)
Background: Human Papilloma Virus (HPV) is considered as a successful pathogen as it has the ability to evade host immune responses and establish long-term persistent infection. Programmed Death Ligand 1 (PDL-1) expression is correlated with HPV-positivity and is increased with lesion progression or tumor metastasis in cervical cancer. The expression of microRNAs (miRNAs) is often deregulated in cancer disease and their potential targets are affected. Methods: RNA was extracted from formalin fixed cervical samples of different histological types, previously typed for the presence of HPV virus. A specific quantitative Polymerase Chain Reaction (qPCR) protocol with SYBR Green was used to check for the expression of four miRNAs that were computationally predicted to target PDL-1. Results and conclusion: hsa-miR-20a-5p and hsa-miR-106b-5p are two miRNAs that showed an expression increase with the severity of the lesions, while hsa-miR-125b-5p depicted a significant decrease in its expression in cancerous samples were compared to normal samples.